ANALISIS PENERAPAN PENGELOLAAN KEUANGAN DANA DESA BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018 (Studi Kasus Pada Desa Melintang Kecamatan Muara Wis Kabupaten Kutai Kartanegara) - Nyoria Anggraeni Mersa (Jurnal Eksis, 2020)
The objectives achieved in this study were to determine the application of Melintang Village financial management based on Permendagri Number 20 of 2018 concerning village financial management. Techniques collection data using triangulation techniques aim to test the truth of data obtained from observation, interviews and documentation from Melintang Village. The results of the discussion that have been described are: (a) village financial planning has been carried out with the principles of community participation and openness, (b) in the implementation of the village government has applied the principle of accountability for revenues and expenditures, but can be seen from the realization of the implementation of the budget allocation for village funds have not been optimally absorbed, especially in the field of implementation of development activities, (c) the administration has been carried out and is periodically accounted to the village head and the community, (d) reporting on the realization of the APBDesa implementation has been submitted to the community as a form of the process of implementing the APBDesa implementation, (e) for accountability reports on the realization of the APBDesa the village head has also submitted to the Regent at the end of the fiscal year.   Keyword : village financial management, internal ministerial regulation